Contribution to the Ecophysiological Study of Four Mediterranean Forest Species (Quercus suber, Ceratonia siliqua, Tetraclinis articulata, Cedrus atlantica) - Mohamed Mouafik; Mohamed Ouajdi; Oumaima Ninich; Jalila Aoujdad; Ahmed El Aboudi (Environmental Sciences Proceedings, 2022)
Forest degradation has been accentuated in recent years by climate change and drought. This study consists of producing quality plants and understanding their ecophysiological behavior in the face of water stress. The plants of two broadleaves (Quercus suber, Ceratonia siliqua) and two conifers (Tetraclinis articulata, Cedrus atlantica) aged 6 months were subjected to water stress. The basic (Ψb) and minimum (Ψm) leaf water potential was measured and processed according to climatic factors for the 4 forest species. The results show that the leaf water potential in Quercus suber presents more negative values (−0.42 MPa) for basic leaf water potential and (−1.43 MPa) for minimum leaf water potential than the other forest species studied. While Cedrus atlantica presents the least negative values for minimum leaf water potential (−0.89 MPa). These results allowed us to define the species that is more resistant to water stress and climate change. However, they refer us to more general questions concerning the mechanisms of water use in forest plants.